(untitled) (Nóema, 2013)
The concept of complexity has a special status within the scientific discourse: because it is used with reference to very different phenomena and processes – ranging from the prebiotic world to the symbolic, mental, and social worlds – it does not seem possible to give a single definition or an unambiguous criterion of measurability. The scientific and philosophical significance of the concept also must be studied in relation to other interdisciplinary issues: self-organization and self-organizing systems, evolution of systems and emergent properties, linearity and non-linearity, scientific reductionism, the relation between map and territory (or representation and reality), the role of the observer. Given the scenario delineated above, the article aims to contribute to a philosophical clarification of the concept of complexity, retracing some key moments in its history from the article by Warren Weaver, “Science and Complexity”, up to the current debate.